Answer:
f - f '= 6.18*10^11 Hz
Step-by-step explanation:
The change in frequency is given by:
![(1)/(f')=(1)/(f)(√(1+v/c))/(√(1-v/c))](https://img.qammunity.org/2021/formulas/physics/middle-school/ie43d0oq78091dfoqgtn6yc707rgk5ip8d.png)
f': observed frequency
f: source frequency = 6.17*10^14 Hz
v: speed of the source = 3.01*10^55 m/s
c: speed of light = 3*10^8 m/s
By replacing all these values you obtain:
![(1)/(f')=(1)/(6.17x10^(14) Hz)(√(1+(3.01*10^5m/s)(3*10^8m/s)))/(√(1-(3.01*10^5m/s)(3*10^8m/s)))=1.62*10^(-15)\\\\f'=6.16*10^(14)Hz](https://img.qammunity.org/2021/formulas/physics/middle-school/23nveq3nsnh6d2jvajc8zsty8yhmy3fjzg.png)
hence, the change in frequency f-f' will be:
f - f '= 6.18*10^11 Hz